Phytochemical studies of Mesua lepidota and Garcinia griffithii with the aid of 13C-NMR DEReplication and their anticholinesterase activities / Leong Sow Tein - Leong , Sow Tein (2024)
Phytochemical studies on Mesua lepidota and Garcinia griffithii, using a 13C-NMR dereplication tool, MixONat were carried out. From the bark hexane extract of M. lepidota, a total of sixteen (16) compounds were identified; of these, eight (8) were identified using the MixONat, while thirteen (13) isolated and purified. Five (5) of these compounds were identified through both the isolation and 13C-NMR dereplication technique. Fifteen (15) of these compounds were already known; sitosterol 174, stigmasterol 173, α-amyrin 194, friedelin 186, friedelinol 189, betulinic acid 177, glutinol 491, lepidotol A 70, B 71 & E 86, lepidotin A 88 and B 89, mammea A/BB cylco F 77, ochrocarpin E 76, pyranojacareubin 164, and one, lepidotin C 490, was new. In addition, the 13C-NMR dereplication (MixONat) on the dichloromethane extract of G. griffithii leaves revealed six (6) compounds, three (3) were isolated. The identified metabolites were (+)-camboginol 253, isoxanthochymol 248, xanthochymol 270 and (+)-cycloxanthochymol 252, garcimultiflorone D 262 and parvifoliol F 492. Three (3) Mammea coumarins exhibited potent inhibition on butyryl cholinesterase (BChE); lepidotin C 490, lepidotin B 89 and mammea A/BB cyclo F 77 with the IC50 values of 1.79±0.07 μM, 1.60±0.26 μM, and 2.24±0.12 μM respectively. Lepidotin B 89 was the most potent inhibitor of BChE, which demonstrated a threefold increase in potency compared to the drug galantamine. It showed a mix-mode inhibition profile, with the inhibition constant, Ki value of 1.03 μM. Molecular docking and molecular dynamics simulations revealed stable interations of lepidotin B 89 with key residues within five critical regions of BChE, which include both active binding sites and allosteric binding sites. This analysis predicted a favourable binding affinity for lepidotin B 89 and facilitated the identification of significant residues crucial for the binding interaction.